Giant City State Park and the Civilian Conservation Corps : a history in words and pictures - Rippelmeyer, Kay, 1953- (Southern Illinois University Press, 2010)
Many recognize Giant City State Park as one of the premier recreation spots in southern Illinois, with its unspoiled forests, glorious rock formations, and famous sandstone lodge. But few know the park's history or are aware of the remarkable men who struggled to build it. Giant City State Park and the Civilian Conservation Corps: A History in Words and Pictures provides the first in-depth portrait of the park's creation, drawing on rarely seen photos, local and national archival research, and interviews to present an intriguing chapter in Illinois history. Kay Rippel.